2022
DOI: 10.3390/antiox11020397
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Cataract Severity Based on Antioxidant Status and Ascorbic Acid Levels in Aqueous Humor

Abstract: Cataract is the leading cause of blindness throughout the world. Currently, the cataract severity evaluation is based on the subjective LOCS III guideline. To ameliorate the evaluation system and develop an objective and quantitative analysis, we investigated the relationships among aqueous humor total antioxidant capacity (AqTAC), ascorbic acid (AqAA) concentration, and cataract severity. In this study, we enrolled 130 cataract patients who underwent phacoemulsification between April 2019 and March 2020. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“… 53 Few reports have mentioned changes in the antioxidant capacity of aqueous humor, with which the lens is in direct contact. Tsao et al 27 reported that ascorbic acid and TAC levels in the aqueous humor have a significant negative correlation with cataract severity, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 53 Few reports have mentioned changes in the antioxidant capacity of aqueous humor, with which the lens is in direct contact. Tsao et al 27 reported that ascorbic acid and TAC levels in the aqueous humor have a significant negative correlation with cataract severity, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“… 26 Ascorbic acid is expected to account for a high proportion of TAC in aqueous humor. 27 Therefore we aimed to determine whether iridectomy per se would alter the antioxidant environment in the aqueous humor by measuring ascorbic acid concentration and total antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely shown that sunlight, as well as incandescent lamps, can represent a risk factor for the health of the eye and especially for the retina. To date, the replacement of incandescent light with a compact fluorescent lamps (CFLs) or light emitting diodes (leds), is particularly diffused and these low energy devices have increased the possibility of phototoxic eye damage [223,224]. On the other hand, oxidative stress, which occurs in case of an overproduction of ROS or a failure of cellular buffering mechanisms, is able to alter the health of the eye by oxidation of biological macromolecules and an imbalance at the molecular and cellular level [225,226].…”
Section: Discussionmentioning
confidence: 99%
“…For this very reason, it would be advisable to use these protective mixtures from the age of 40 years onwards. This can be explained by the need to not already have accumulated excessive amounts of ROS related to aging, to avoid undergoing demanding pharmacological treatments that may affect oxidative stress and have not been subjected to an excess of adverse environmental factors [ 274 , 275 ].…”
Section: Antioxidant Mixtures To Protect/reduce Eye Diseasesmentioning
confidence: 99%